Internet of things based agricultural drought detection system: case study Southern Somalia - Dahir, Abdukadir; Omar, Mohamed; Abukar, Yahye (Bulletin of Electrical Engineering and Informatics, 2023)
Drought is defined as a protracted lack of precipitation that lasts at least a season, resulting in a water deficit that affects plants, animals, and humans. It is a widespread and repeating feature of climate change in practically all temperate zones, ranging from excessively wet to burned. In Somalia, the government and farmers lack the technological skills to identify and monitor recurrent environmental issues. Our research created a technique for detecting droughts early on to reduce their impact. Using internet of things (IoT) devices, we created a system that measures temperature, humidity, and soil moisture. We then examined the data and used a line chart to show it in a web application (PHP and MySQL). The device reads these environmental parameters using an Arduino Uno, a DHT11 sensor, and a soil moisture sensor. The system deployed provides a real-time, cost-effective method for monitoring and controlling drought in modern agriculture.